Inventory cost calculation for public cleansing management-web based / Mohd Najmuddin Khadirun - Khadirun, Mohd Najmuddin (2018)
Environment Idaman Sdn Bhd company use Geographical Information System (GIS) in the process of data collection until data processing in order to calculate the inventory costing. The data will through the process of reducing error and verifying process to ensure the accuracy of the data which actually consuming a lot of time and it is can be considered as complicated process. The company expect that a system can be built to solve the problem or improve the system that they are currently used. So, this study is carried out to improve the data processing by producing a database by using model builder which is used to calculate the cost for all of the data based on each feature and it rate for costing. A system is creating to show all of data in the map format included all of the attribute data which has been created by using model builder. The system is created using ArcGIS online which can synchronize with the ArcGIS software that used by the company. Users can use the web application in order to manage their financial costing of public cleansing management.